Aortic root enlargement versus stentless valve implantation for avoidance of patient-prosthesis mismatch in patients with small aortic root: protocol for a systematic review - Siamak Mohammadi; Fatouma Sall; Herve Yangni-Angate; Pierre Voisine; François Dagenais; Christophe Meneas; Carlos Mestres; Remi Kabore; Anon N'guessan (BMJ Open, 2024)
Introduction Avoiding patient-prosthesis mismatch (PPM) in patients with small aortic annulus (SAA) during aortic valve replacement (AVR) is still a challenging surgical problem. Among surgical options available, aortic root enlargement (ARE) and stentless valve implantation (SVI) are the two most commonly used strategies. This systematic review will be conducted searching for superiority evidence based on comparative studies between these two options.Methods and analysis This systematic review will include all relevant articles published from 1 January 1946 to 31 March 2024, with available full texts from Medline (Ovid), Embase, Cochrane Library and Web of Science databases, without any language restriction. Observational studies and randomised controlled trials comparing surgical results of ARE versus SVI for AVR in patients with small aortic root will be screened. Studies will be classified into three groups: group 1 for studies that reported SVI or other tissue valve outcomes without comparing them with ARE outcomes; group 2 for studies that reported ARE outcomes without comparing them with SVI outcomes; and group 3 for studies that compared ARE outcomes with SVI outcomes. The quality of the evidence of each study will be evaluated according to Oxford Centre for Evidence-Based Medicine criteria.Ethics and dissemination Ethical approval is not required because no primary data are collected. The findings will be presented at scientific conferences and/or reported in a peer-reviewed scientific journal.Trial registration number PROSPERO, CRD42023383793.